Marketing Strategy and Procedures for Using the Hasanah Card at Bank XYZ Yogyakarta Area - Anggraeni, Silvia Fatma; Muhammad, Rifqi (Formosa Journal of Applied Sciences, 2024)
Sharia banks are institutions that provide banking services in accordance with Islamic sharia principles. One of the products owned by sharia banks is Hasanah cards. Hasanah card is a financing card that functions like a credit card based on sharia principles that can be used to carry out transactions. This research uses primary data through observation, interviews, and collecting documents from companies. The focus of this research is to find out the right strategy to increase the use of hasanah cards, procedures for applying for hasanah cards, and what obstacles are experienced in marketing hasanah cards. The results of this research show that (1) the strategy carried out is not optimal (2) the procedure is carried out via telephone at the head office, bundling, and submissions from branches (3) the obstacles experienced by many people are not yet familiar with Hasanah cards and a lack of awareness from marketing.